Model Penal Code: Sentencing—Workable Limits on Mass Punishment - Reitz, Kevin R. (Crime and justice, 2019)
The Model Penal Code: Sentencing (MPCS) rewrites the 1962 Model Penal Code’s provisions on sentencing and corrections. Since the 1960s, use of all forms of punishment has exploded, including incarceration, community supervision, supervision revocation, economic sanctions, and collateral consequences of convictions. The MPCS provides an institutional framework for all major forms of punishment. It consists of a sentencing commission, sentencing guidelines, abolition of parole release discretion, appellate sentence review, and controls on correctional population size. It revamps sentencing procedures to inject greater fairness and transparency. It gives state legislators broad advice on how they can reform their systems as a whole, while improving decisions in each case. The MPCS recommends newly crafted limits on punishment through reasoned pursuit of utilitarian crime reduction goals, prohibition of disproportionate sentence severity, individualization of sentences that cuts through even mandatory minimum penalties, refinement of each type of punishment so it can achieve its core purposes, an attack on “criminogenic” sentences that do more harm than good, measures to prioritize and direct correctional resources to offenders who present the greatest risks and highest needs, and creation of institutional capacity to monitor, manage, and improve the entire system over time.